Reflective Practice and Learning From Mistakes in Social Work - Sicora, Alessandro (Book collections on Project MUSE., 2017)
What is a mistake in social work and how can we turn it into a positive learning experience? Simply going over the events of the day is often not enough and can become overwhelming. Learning from professional errors is, however, vital for successful reflective practice. This important book presents a theoretical framework that underpins this learning, along with a series of strategies for social workers to use either by themselves or as part of a group. These include creating questions and narratives to enhance learning, assertive techniques for receiving and offering criticism and organisational learning from mistakes.